(ﻣﻌﺎھدات اﻟﺻﻠﺢ اﻟﺗﻲ وردت ﻧﺻﺎ ﻟﻣدن وﺳط ﺑﻼد ﻓﺎرس وﺟﻧوﺑﮭﺎ (ﺑﺣث ﻣﺳﺗل ﻣن اطروﺣﺔ دﻛﺗوراه - أ.د.ﺟﺎﺳم ﺻﻛﺑﺎن ﻋﻠﻲ م.د.ﺑﮭﺟﺔ ﻋﻠﻲ ﻣﺣﻣد ﻛرﯾم (College of Education for Women, 2019)
The process of the Islamic conquste and truces treaties for the north Persian country people are happened more than other parts of the country, because it has the famous towns with the economical movements. We have noticed that the passages of the truces treaties, which are written in the AL-Tabree book, and Ibn-Alatheer history book, and AL-Balatheree book with shorten notices, and some them are difference from the passages of ALTabree, we think that historians aren't written of them because they are thought these passages aren't nesseccory of written, and which have tired for the readers.